First‐Principles Exploration of 2D Benzenehexathiolate Coordination Nanosheets for Broadband Electrochromic Devices. (7th August 2022) - Li, Meng; Wu, Zhenzhen; Zheng, Mengting; Chen, Hao; Gould, Tim; Zhang, Shanqing
Abstract: Electrochromic materials can tune the illumination and heat exchange of a building with the environment and thereby save energy in lighting, heating, and air conditioning in a cost‐effective way, which is vital in realizing carbon neutrality. 2D frameworks such as coordination nanosheets (CONASHs) that are widely explored for a wide range of applications in energy storage and conversion can be a cluster of novel electrochromic materials. In this work, a series of transition metal benzenehexathiol (TM‐BHT) CONASHs are theoretically investigated via first‐principles simulations. During ion intercalation and deintercalation in TM‐BHTs, changes in lattice structures, lithium diffusion barriers, atomic charges, bond strength, and electronic properties are explored in‐depth. The incurred changes are then correlated with critical electrochromic properties, including the transmittance adjustment ranges in the visible light, near‐infrared, solar spectrum, and mid‐infrared. Among the various TM‐BHT systems, Cu‐BHT and Ag‐BHT are the most promising broadband electrochromic materials for optical and thermal management in the wavelength range from visible to mid‐infrared. The theoretical guidance from this work paves a new path toward electrochromic applications of CONASHs that exploit the versatility of these 2D materials. Abstract : A series of transition metal benzenehexathiol (TM‐BHT) coordination nanosheets are theoretically investigated for their structure‐property relationship during lithium intercalation. Among them, Cu‐BHT and Ag‐BHT are predicted to have the broadest color changes and the largest modulation ranges in the solar spectrum and mid‐infrared, which facilitates electrochromic applications for optical and thermal management.